1985
DOI: 10.1037/0022-006x.53.5.704
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder among Army Nurse Corps Vietnam veterans.

Abstract: Results are presented from an epidemiologic investigation of posttraumatic stress disorder (PTSD) among Army nurse veterans. Analysis of questionnaire data from more than 700 Vietnam and Vietnam-era veterans still on active duty in the U.S. Army Nurse Corps reveals a current PTSD rate for Vietnam veteran nurses of 3.3%. This rate is comparable to that found among nonnurse active duty Army Vietnam veterans (5.1%) and is much lower than estimates (18%-54%) for civilian Vietnam veterans. Results suggest that dang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 11 publications
2
32
0
Order By: Relevance
“…Most of these women had little or no previous military experience, and may have been unprepared for dealing with the death and destruction of war, or perhaps the negative reaction received at homecoming. Not surprisingly, some of the adjustment difficulties that have been described in male Vietnam veterans have also been observed among female veterans, including symptoms of PTSD (Stretch, Vail, & Maloney, 1985). The NVVRS (Kulka et al, 1990a) revealed a PTSD rate of 8.5% among female theater veterans (those serving in Vietnam or its surrounding waters or air space during wartime), and an additional 7.2% displayed partial PTSD presentations.…”
mentioning
confidence: 96%
“…Most of these women had little or no previous military experience, and may have been unprepared for dealing with the death and destruction of war, or perhaps the negative reaction received at homecoming. Not surprisingly, some of the adjustment difficulties that have been described in male Vietnam veterans have also been observed among female veterans, including symptoms of PTSD (Stretch, Vail, & Maloney, 1985). The NVVRS (Kulka et al, 1990a) revealed a PTSD rate of 8.5% among female theater veterans (those serving in Vietnam or its surrounding waters or air space during wartime), and an additional 7.2% displayed partial PTSD presentations.…”
mentioning
confidence: 96%
“…In their study of active duty Army nurses, Stretch et al, (1985) found that 72% of subjects stated that their service in Vietnam had a positive impact on their lives and 62% reported that they would be willing to serve in a similar war in the future. In their study of active duty Army nurses, Stretch et al, (1985) found that 72% of subjects stated that their service in Vietnam had a positive impact on their lives and 62% reported that they would be willing to serve in a similar war in the future.…”
mentioning
confidence: 99%
“…or blunted (reduced) emotional reactions rather than anxiety. A number of studies, however, suggest that PTSD may legitimately represent a "delayed" reaction to anxiety-provoking stimuli (see Stretch, Vail, & Maloney, 1985).…”
Section: Abnormal and Normal Emotional Reactionsmentioning
confidence: 99%